Cognitive requirements and ergonomic criteria in designing digital learning platforms - amrane, hacene; bouziane, mourad (Journal of Social Sciences and Humanities, 2025)
The article aims to introduce designers of digital learning platforms to consider cognitive aspects of the learners in the design and the development of these platforms. Indeed, the screen remains a specific environment for learner cognition. Learning online requires a particular arrangement of the tools made available to the learner. The latter must therefore deal with objects and routes coming from a reality other than their own. Thus, ergonomics is called upon to anticipate the specificity of cognitive operations linked to an online learning activity. This article proposes in this continuity to pose the arguments pleading for an ergonomic design integrative of the mental dimensions specific to this type of learning environment.